2017
DOI: 10.1038/s41598-017-07215-7
|View full text |Cite
|
Sign up to set email alerts
|

Zinc binding to RNA recognition motif of TDP-43 induces the formation of amyloid-like aggregates

Abstract: Aggregation of TDP-43 (transactive response DNA binding protein 43 kDa) is a hallmark of certain forms of amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration (FTLD). Moreover, intracellular TDP-43-positive inclusions are often found in other neurodegenerative diseases. Recently it was shown that zinc ions can provoke the aggregation of endogenous TDP-43 in cells, allowing to assume a direct interaction of TDP-43 with zinc ions. In this work, we investigated zinc binding to the 102–269 TDP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 60 publications
4
62
0
Order By: Relevance
“…Zinc, which plays an important role in many physiological processes, has been implicated in the molecular mechanisms of many NDs by favoring aggregation of proteins such as amyloid beta, FUS, TDP-43 [21,30]. Recent in vitro studies showed that zinc could also impact Tau aggregation into PHF, a hallmark of several tauopathies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zinc, which plays an important role in many physiological processes, has been implicated in the molecular mechanisms of many NDs by favoring aggregation of proteins such as amyloid beta, FUS, TDP-43 [21,30]. Recent in vitro studies showed that zinc could also impact Tau aggregation into PHF, a hallmark of several tauopathies.…”
Section: Discussionmentioning
confidence: 99%
“…Four microliters of incubated Tau samples (30 μM) was placed on carbon-coated copper grids (300 mesh) for 1 min. After blotting, grids were washed with distilled water and blotted again, and negatively stained for 30 s with 2% (wt/vol) uranyl acetate as previously described [21]. The grids were then dried and observed with a JEOL 2200FS transmission electron microscope (Tokyo, Japan) operating at 200 kV.…”
Section: Transmission Electron Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…The thermostability of MAPK14 was measured in the presence of different concentrations of MBZ in 50 mM HEPES buffer in the presence of 200 mM NaCl and 2% DMSO at pH 7.5 using a label-free fluorimetric analysis with a Prometheus NT.Plex instrument (NanoTemper Technologies), as described previously [52]. NanoDSF grade capillaries were filled with a 10 µM solution of interest.…”
Section: Nano Differential Scanning Fluorimetry Assaymentioning
confidence: 99%
“…12:301. doi: 10.3389/fnmol.2019.00301 In the original article, there was an error. In "Binding of Zinc was shown to increase TDP-43 thermostability and formed Thioflavin-T-positive aggregates, reminiscent of amyloid nuclei (Garnier et al, 2017)." The word "increase" should be replaced by "decrease".…”
Section: A Corrigendum Onmentioning
confidence: 99%